Pre-Service Teachers’ Skills in Analyzing the Mathematics Competency Based on Bloom Taxonomy - Vita Istihapsari; Afit Istiandaru; Siti Nur Rohmah (International Journal on Emerging Mathematics Education, 2019)
Professional teachers need to be skilled in planning their lesson. One of the activities to plan the lesson is analyzing the competence and teaching material demanded by the curriculum. This article aims to describe the Indonesian pre-service mathematics teachers’ skills in analyzing junior high school mathematics competence. The analysis is important to prepare the appropriate material for their students. This is qualitative research involving 26 pre-service teachers enrolled in the subject of Curriculum Analysis for Junior High School. First, they were assigned to analyze a given basic competence and were then challenged to select the appropriate materials and the indicators when the competence achieved according to Bloom taxonomy. Surprisingly, though there are many reference books available for sources of analysis, the teacher candidates found some difficulties in arranging the topics and composing the appropriate indicators. Some errors found such as the use of unmeasurable verbs, unclear activities, and illogical-irrelevant topics.